Dissolved and Suspended Polycyclic Aromatic Hydrocarbons (PAH) in the North Aegean Sea - HATZIANESTIS, I.; SKLIVAGOU, E. (Mediterranean Marine Science, 2002)
The distribution and sources of polycyclic aromatic hydrocarbons (PAH) were investigated in the seawater of the North Aegean Sea. The measured PAH concentrations in SPM are generally considered as elevated for open sea waters and were evenly distributed in the area. Their levels in the dissolved phase (1.6-33.0 ng/l) were much higher than those encountered in the corresponding particulate phases (0.04-10.2 ng/l). The PAH patterns in both phases were dominated by the three ring aromatics and their alkylated derivatives, reflecting a predominant contribution of fossil hydrocarbons probably related to ship traffic, whereas no significant inputs from the rivers outfalling in the area were detected. In bottom waters PAH values were generally lower, whereas a higher depletion of the petroleum PAH in comparison with the pyrolytic ones according to depth was observed.